Interaction between extracellular matrix molecules and microbial pathogens: evidence for the missing link in autoimmunity with rheumatoid arthritis as a disease model - Sofat, Nidhi; Wait, Robin; Robertson, Saralili D.; Baines, Deborah L.; Baker, Emma H. (Frontiers in Microbiology, 2015)
Rheumatoid arthritis (RA) is an autoimmune disease characterised by inflammation, tissue rebuilding and fibrosis. Inability by the body to regulate inflammation effectively is one of the hallmarks of RA. Interactions between the external environment and the human host play an important role in the development of autoimmunity. In RA, the observation of anti-cyclic citrullinated peptide antibodies (ACPA) to autoantigens is well recognised. Citrullination is a post-translational modification mediated by peptidyl arginine deiminases (PADs), which exist in both mammalian and bacterial forms. Previous studies have shown how proteins expressed in the human extracellular matrix (ECM) acquire properties of damage-associated molecular patterns (DAMPs) in RA and include collagens, tenascin-C and fibronectin. ECM DAMPs can further potentiate tissue damage in RA. Recent work has shown that citrullination in RA occurs at mucosal sites, including the oral cavity and lung. Mucosal sites have been linked with bacterial infection e.g. periodontal disease, where exogenous pathogens are implicated in the development of autoimmunity via an infectious trigger. Here we explore how mucosal surfaces exposed to bacteria could trigger autoimmunity in RA.